Tracing the route to organisational performance through expatriate leadership effectiveness: the role of emotional, cultural and spiritual intelligence - Haque, A. K. M. Ahasanul; Chowdhury, Naila Anwar; Islam, Md Asadul; Hossain, Md Shahadat; Sarker, Md Atiqur (Inderscience Publishers, 2024)
This study aims to determine the effects of emotional, cultural and spiritual intelligence on organisational performance through expatriate leadership effectiveness. For doing so, a conceptual framework has been designed. Afterwards, data were collected from expatriate managers of various multinational corporations in Kuala Lumpur, Malaysia, through the employment of self-administered questionnaires. The collected data were later analysed through SPSS and SEM. The outcomes indicated that cultural and spiritual intelligence have positive effects on expatriate leadership effectiveness. Furthermore, emotional, cultural and spiritual intelligence and expatriate leadership effectiveness have positive effects on organisational performance. The results have also shown that expatriate leadership effectiveness mediates the relationship between cultural and spiritual intelligence and organisational performance. Implications, limitations and future research directions are discussed.